Resin composition, optical fiber, and method for producing optical fiber

A resin composition with urethane (meth)acrylate, aliphatic epoxy (meth)acrylate, and hydrophobic inorganic oxide particles forms a secondary resin layer that enhances both Young's modulus and toughness in optical fibers, addressing the challenge of maintaining resilience under lateral pressure.

JP7609066B2Active Publication Date: 2025-01-07SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021527616
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-17
Filing Date
2020-06-08
Publication Date
2025-01-07
Estimated Expiration
2040-06-08

AI Technical Summary

Technical Problem

Optical fibers require a secondary resin layer with high Young's modulus to resist lateral pressure while maintaining toughness, as the secondary resin layer's toughness tends to decrease with increased modulus.

Method used

A resin composition containing urethane (meth)acrylate and aliphatic epoxy (meth)acrylate, with specific content ratios, and hydrophobic inorganic oxide particles is used to form a secondary resin layer that balances high Young's modulus and toughness.

Benefits of technology

The resin composition achieves both high Young's modulus and toughness, improving the lateral pressure characteristics and durability of optical fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609066000004
    Figure 0007609066000004
  • Figure 0007609066000001
    Figure 0007609066000001
  • Figure 0007609066000002
    Figure 0007609066000002
Patent Text Reader

Abstract

A resin composition for optical fiber coating according to the present invention contains: a base resin that contains a photopolymerizable compound and a photopolymerization initiator; and hydrophobic inorganic oxide particles. The photopolymerizable compound contains a urethane (meth)acrylate and an aliphatic epoxy (meth)acrylate; and the content of the aliphatic epoxy (meth)acrylate is from 1.0% by mass to 45% by mass (inclusive) based on the total mass of the photopolymerizable compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, an optical fiber, and a method for producing an optical fiber. This application claims priority to Japanese Application No. 2019-112037, filed on June 17, 2019, and incorporates by reference all of the contents of said Japanese application. [Background technology]

[0002] The optical fiber has a coating resin layer for protecting the glass fiber, which is an optical transmission medium. The coating resin layer generally includes a primary resin layer and a secondary resin layer. In order to reduce an increase in transmission loss induced by minute bending that occurs when lateral pressure is applied to the optical fiber, the optical fiber is required to have excellent lateral pressure characteristics.

[0003] In Patent Document 1, it is considered that the lateral pressure characteristics of the optical fiber can be improved by incorporating a filler in the outermost layer of the coating resin layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-219550 A Summary of the Invention

[0005] A resin composition according to one embodiment of the present disclosure contains a base resin including a photopolymerizable compound and a photopolymerization initiator, and hydrophobic inorganic oxide particles, wherein the photopolymerizable compound includes a urethane (meth)acrylate and an aliphatic epoxy (meth)acrylate, and the content of the aliphatic epoxy (meth)acrylate is 1.0 mass% or more and 45 mass% or less based on the total amount of the photopolymerizable compound. [Brief description of the drawings]

[0006] [Figure 1]FIG. 1 is a schematic cross-sectional view showing an example of an optical fiber according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] [Problem that this disclosure aims to solve] A secondary resin layer containing a filler has a high Young's modulus and is therefore less susceptible to the effects of lateral pressure, but its toughness tends to decrease, so the secondary resin layer is required to have excellent toughness while maintaining a high Young's modulus.

[0008] An object of the present disclosure is to provide a resin composition that can achieve both high Young's modulus and toughness, and an optical fiber including a secondary resin layer formed from the resin composition.

[0009] [Effects of this disclosure] According to the present disclosure, it is possible to provide a resin composition that can achieve both high Young's modulus and toughness, and an optical fiber including a secondary resin layer formed from the resin composition.

[0010] [Description of the embodiments of the present disclosure] First, the contents of the embodiment of the present disclosure will be listed and described. A resin composition according to one aspect of the present disclosure contains a base resin including a photopolymerizable compound and a photopolymerization initiator, and hydrophobic inorganic oxide particles, the photopolymerizable compound includes a urethane (meth)acrylate and an aliphatic epoxy (meth)acrylate, and the content of the aliphatic epoxy (meth)acrylate is 1.0 mass% or more and 45 mass% or less based on the total amount of the photopolymerizable compound.

[0011] Such a resin composition can be used as a resin composition for coating an optical fiber to form a secondary resin layer that can achieve both high Young's modulus and toughness.

[0012] In order to further increase the toughness of the secondary resin layer, the aliphatic epoxy (meth)acrylate may have an ethylene oxide group or a propylene oxide group.

[0013] In order to impart appropriate toughness to the secondary resin layer, the photopolymerizable compound may further contain an epoxy (meth)acrylate having an aromatic ring.

[0014] The inorganic oxide particles may be particles containing at least one selected from the group consisting of silicon dioxide, zirconium dioxide, aluminum oxide, magnesium oxide, titanium oxide, tin oxide, and zinc oxide, because they have excellent dispersibility in the resin composition and allow easy adjustment of the Young's modulus.

[0015] An optical fiber according to an embodiment of the present disclosure includes a glass fiber including a core and a cladding, a primary resin layer that contacts the glass fiber and coats the glass fiber, and a secondary resin layer that coats the primary resin layer, the secondary resin layer including a cured product of the resin composition, thereby making it possible to improve the lateral pressure characteristics and toughness of the optical fiber.

[0016] The method for producing an optical fiber according to an embodiment of the present disclosure includes a coating step of coating the resin composition on the outer periphery of a glass fiber composed of a core and a cladding, and a curing step of curing the resin composition by irradiating it with ultraviolet light after the coating step, thereby making it possible to produce an optical fiber having improved lateral pressure characteristics and toughness.

[0017] [Details of the embodiment of the present disclosure] Specific examples of the resin composition and optical fiber according to the embodiment of the present disclosure will be described with reference to the drawings as necessary. Note that the present invention is not limited to these examples, but is indicated by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. In the following description, the same elements in the description of the drawings will be given the same reference numerals, and duplicated descriptions will be omitted.

[0018] <Resin composition> The resin composition according to the present embodiment contains a base resin containing a photopolymerizable compound and a photopolymerization initiator, and hydrophobic inorganic oxide particles.

[0019] (Base resin) The photopolymerizable compound according to the present embodiment includes urethane (meth)acrylate and aliphatic epoxy (meth)acrylate. Here, the (meth)acrylate means an acrylate or a corresponding methacrylate. The same applies to (meth)acrylic acid.

[0020] As the urethane (meth)acrylate, an oligomer obtained by reacting a polyol compound, a polyisocyanate compound, and a hydroxyl group-containing (meth)acrylate compound can be used. The urethane (meth)acrylate has a urethane structure based on the reaction between a polyol compound and a polyisocyanate compound, and a (meth)acryloyl group bonded to the end of the urethane structure.

[0021] Examples of polyol compounds include polytetramethylene glycol, polypropylene glycol, and bisphenol A-ethylene oxide addition diol. Examples of polyisocyanate compounds include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate. Examples of hydroxyl group-containing (meth)acrylate compounds include 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, 2-hydroxypropyl (meth)acrylate, and tripropylene glycol mono(meth)acrylate.

[0022] From the viewpoint of adjusting the Young's modulus of the resin layer, the number average molecular weight (Mn) of the polyol compound is preferably 300 or more and 4,000 or less, more preferably 400 or more and 3,000 or less, and even more preferably 500 or more and 2,500 or less.

[0023] In general, an organic tin compound is used as a catalyst when synthesizing urethane (meth)acrylate. Examples of the organic tin compound include dibutyltin dilaurate, dibutyltin diacetate, dibutyltin maleate, dibutyltin bis(2-ethylhexyl mercaptoacetate), dibutyltin bis(isooctyl mercaptoacetate) and dibutyltin oxide. In terms of easy availability or catalytic performance, it is preferable to use dibutyltin dilaurate or dibutyltin diacetate as a catalyst.

[0024] A lower alcohol having 5 or less carbon atoms may be used during synthesis of the urethane (meth)acrylate. Examples of the lower alcohol include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methyl-2-propanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, 3-methyl-1-butanol, 2-methyl-2-butanol, 3-methyl-2-butanol, and 2,2-dimethyl-1-propanol.

[0025] The content of the urethane (meth)acrylate may be from 1% by mass to 30% by mass, from 5% by mass to 20% by mass, or from 10% by mass to 15% by mass, based on the total amount of the photopolymerizable compounds.

[0026] As the aliphatic epoxy (meth)acrylate, an oligomer obtained by reacting an aliphatic epoxy compound having two or more glycidyl groups with a compound having a (meth)acryloyl group such as (meth)acrylic acid can be used. The aliphatic epoxy (meth)acrylate is an epoxy (meth)acrylate that does not have an aromatic ring.

[0027] In order to further increase the toughness of the secondary resin layer, the aliphatic epoxy (meth)acrylate preferably has an ethylene oxide (EO) group or a propylene oxide (PO) group. Examples of the aliphatic epoxy (meth)acrylate include a (meth)acrylic acid adduct of propylene glycol diglycidyl ether, a (meth)acrylic acid adduct of polypropylene glycol diglycidyl ether, a (meth)acrylic acid adduct of ethylene glycol diglycidyl ether, and a (meth)acrylic acid adduct of polyethylene glycol diglycidyl ether.

[0028] As the aliphatic epoxy (meth)acrylate, a compound represented by the following formula (1) or (2) may be used. 1 and R 2 each independently represents a hydrogen atom or a methyl group, and n and m each independently represent an integer of 0 or greater than 1. n and m may be an integer of 1 or greater and 10 or less, an integer of 1 or greater and 9 or less, or an integer of 2 or greater and 9 or less. [ka]

[0029] Commercially available aliphatic epoxy (meth)acrylate products include, for example, trade names "EPOXY ESTER 40EM," "EPOXY ESTER 70PA," "EPOXY ESTER 200PA," and "EPOXY ESTER 80MFA" manufactured by Kyoeisha Chemical Co., Ltd.

[0030] In order to impart flexibility to the resin layer and achieve both high Young's modulus and toughness, the content of the aliphatic epoxy (meth)acrylate is from 1.0 mass% to 45 mass% based on the total amount of the photopolymerizable compound, preferably from 1.5 mass% to 40 mass%, more preferably from 3 mass% to 35 mass%, and even more preferably from 4 mass% to 32 mass%.

[0031] Since the photopolymerizable compound has an excellent balance between Young's modulus and toughness, the photopolymerizable compound may further contain an epoxy (meth)acrylate having an aromatic ring. As the epoxy (meth)acrylate having an aromatic ring, an oligomer obtained by reacting an aromatic epoxy compound having two or more glycidyl groups with a compound having a (meth)acryloyl group such as (meth)acrylic acid can be used. As the epoxy (meth)acrylate having an aromatic ring, for example, a (meth)acrylic acid adduct of bisphenol A diglycidyl ether can be mentioned. The content of the epoxy (meth)acrylate having an aromatic ring may be 10% by mass or more and 50% by mass or less, 20% by mass or more and 45% by mass or less, or 30% by mass or more and 45% by mass or less based on the total amount of the photopolymerizable compound.

[0032] In this specification, the urethane (meth)acrylate and epoxy (meth)acrylate used as the photopolymerizable compound may be collectively referred to as "oligomer." The photopolymerizable compound according to this embodiment may further contain a photopolymerizable compound other than the oligomer (hereinafter referred to as "monomer").

[0033] As the monomer, at least one selected from the group consisting of a monofunctional monomer having one photopolymerizable group and a polyfunctional monomer having two or more photopolymerizable groups can be used. Two or more types of monomers may be mixed and used.

[0034] Examples of monofunctional monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, s-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, isoamyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. , n-octyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 3-phenoxybenzyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 4-tert-butylcyclohexanol acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, (meth)acrylate monomers such as acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, nonylphenol polyethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid, (meth)acrylic acid dimer, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, and ω-carboxy-polycaproic acid dimer. Carboxyl group-containing monomers such as lactone (meth)acrylates; heterocycle-containing monomers such as N-(meth)acryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N-acryloylpiperidine, N-methacryloylpiperidine, N-(meth)acryloylpyrrolidine, 3-(3-pyridine)propyl (meth)acrylate, and cyclic trimethylolpropane formal acrylate; maleimide-based monomers such as maleimide, N-cyclohexylmaleimide, and N-phenylmaleimide;Amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; aminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, aminopropyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate; and succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide.

[0035] Examples of polyfunctional monomers include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, di(meth)acrylate of alkylene oxide adduct of bisphenol A, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, and the like. meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 1,14-tetradecanediol di(meth)acrylate, 1,16-hexadecanediol di(meth)acrylate, 1,20-eicosanediol di(meth)acrylate, isopentyldiol di(meth)acrylate, 3-ethyl-1,8-octanediol di(meth)acrylate, EO adduct di(meth)acrylate of bisphenol A Monomers having two polymerizable groups such as trimethylolpropane tri(meth)acrylate, trimethyloloctane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, trimethylolpropane polypropoxy tri(meth)acrylate, trimethylolpropane polyethoxy polypropoxy tri(meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol polyethoxy tri(meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol polyethoxy tri(meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, pentaerythritol polyethoxy ... Examples of monomers having three or more polymerizable groups include monomers having three or more polymerizable groups such as acryloyloxytetra(meth)acrylate, pentaerythritol polypropoxytetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified tris[(meth)acryloyloxyethyl]isocyanurate.

[0036] The photopolymerization initiator can be appropriately selected from known radical photopolymerization initiators. Examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, manufactured by IGM Resins), 2,2-dimethoxy-2-phenylacetophenone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one (Omnirad 907, manufactured by IGM Resins), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO, manufactured by IGM Resins) and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins).

[0037] The content of the photopolymerization initiator is preferably from 0.2 to 6.0% by mass, more preferably from 0.4 to 3.0% by mass, and even more preferably from 0.6 to 2.0% by mass, based on the total amount of the photopolymerizable compound.

[0038] The resin composition may further contain a silane coupling agent, a leveling agent, a defoaming agent, an antioxidant, a sensitizer, and the like.

[0039] The silane coupling agent is not particularly limited as long as it does not interfere with the curing of the resin composition. Examples of the silane coupling agent include tetramethyl silicate, tetraethyl silicate, mercaptopropyl trimethoxysilane, vinyl trichlorosilane, vinyl triethoxysilane, vinyl tris(β-methoxy-ethoxy)silane, β-(3,4-epoxycyclohexyl)-ethyl trimethoxysilane, dimethoxydimethylsilane, diethoxydimethylsilane, 3-acryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-(β-aminoethyl)- Examples of such silanes include γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, bis-[3-(triethoxysilyl)propyl]tetrasulfide, bis-[3-(triethoxysilyl)propyl]disulfide, γ-trimethoxysilylpropyldimethylthiocarbamyltetrasulfide, and γ-trimethoxysilylpropylbenzothiazyltetrasulfide.

[0040] (Inorganic oxide particles) The inorganic oxide particles according to the present embodiment have their surfaces hydrophobically treated. The hydrophobic treatment according to the present embodiment refers to the introduction of a hydrophobic group to the surface of the inorganic oxide particles. The inorganic oxide particles having the hydrophobic group introduced thereto have excellent dispersibility in the resin composition. The hydrophobic group may be a reactive group such as a (meth)acryloyl group or a vinyl group, or a non-reactive group such as an aliphatic hydrocarbon group (e.g., an alkyl group) or an aromatic hydrocarbon group (e.g., a phenyl group). When the inorganic oxide particles have a reactive group, it becomes easier to form a resin layer having a high Young's modulus.

[0041] The inorganic oxide particles according to the present embodiment are dispersed in a dispersion medium. By using the inorganic oxide particles dispersed in a dispersion medium, the inorganic oxide particles can be uniformly dispersed in the resin composition, and the storage stability of the resin composition can be improved. The dispersion medium is not particularly limited as long as it does not inhibit the curing of the resin composition. The dispersion medium may be reactive or non-reactive.

[0042] As the reactive dispersion medium, monomers such as (meth)acryloyl compounds and epoxy compounds may be used. As the (meth)acryloyl compounds, for example, 1,6-hexanediol di(meth)acrylate, EO modified bisphenol A di(meth)acrylate, polyethylene glycol di(meth)acrylate, PO modified bisphenol A di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate may be used. As the (meth)acryloyl compounds, compounds exemplified as the monomers described above may be used.

[0043] As the non-reactive dispersion medium, a ketone solvent such as methyl ethyl ketone (MEK), an alcohol solvent such as methanol (MeOH), or an ester solvent such as propylene glycol monomethyl ether acetate (PGMEA) may be used. In the case of a non-reactive dispersion medium, a resin composition may be prepared by mixing a base resin and inorganic oxide particles dispersed in the dispersion medium, and then removing a part of the dispersion medium.

[0044] The inorganic oxide particles dispersed in the dispersion medium remain dispersed in the resin layer even after the resin composition is cured. When a reactive dispersion medium is used, the inorganic oxide particles are mixed into the resin composition together with the dispersion medium, and are incorporated into the resin layer while maintaining the dispersed state. When a non-reactive dispersion medium is used, at least a part of the dispersion medium is evaporated from the resin composition, but the inorganic oxide particles remain dispersed in the resin composition and remain dispersed in the resin layer after curing. When the inorganic oxide particles present in the resin layer are observed with an electron microscope, the primary particles are observed to be dispersed.

[0045] The inorganic oxide particles are preferably particles containing at least one selected from the group consisting of silicon dioxide (silica), zirconium dioxide (zirconia), aluminum oxide (alumina), magnesium oxide (magnesia), titanium oxide (titania), tin oxide, and zinc oxide, because they have excellent dispersibility in the resin composition and are easy to form a tough resin layer. From the viewpoints of being inexpensive, being easy to subject to surface treatment, having ultraviolet transmittance, and being easy to impart appropriate hardness to the resin layer, it is more preferable to use hydrophobic silica particles as the inorganic oxide particles according to this embodiment.

[0046] From the viewpoint of imparting appropriate toughness to the secondary resin layer, the average primary particle size of the inorganic oxide particles may be 500 nm or less, preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. From the viewpoint of increasing the Young's modulus of the secondary resin layer, the average primary particle size of the inorganic oxide particles is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. The average primary particle size can be measured, for example, by image analysis of an electron microscope photograph, a light scattering method, a BET method, or the like. The dispersion medium in which the primary particles of the inorganic oxide are dispersed appears transparent to the naked eye when the particle size of the primary particles is small. When the particle size of the primary particles is relatively large (40 nm or more), the dispersion medium in which the primary particles are dispersed appears cloudy, but no sediment is observed.

[0047] The content of the inorganic oxide particles is preferably 1% by mass or more and 60% by mass or less, more preferably 5% by mass or more and 55% by mass or less, even more preferably 10% by mass or more and 50% by mass or less, and even more preferably 20% by mass or more and 45% by mass or less, based on the total amount of the photopolymerizable compound and the inorganic oxide particles. When the content of the inorganic oxide particles is 1% by mass or more, it is easy to increase the Young's modulus of the resin layer. When the content of the inorganic oxide particles is 60% by mass or less, it is easy to impart toughness to the resin composition.

[0048] The resin composition according to the present embodiment can be suitably used as a secondary coating material for an optical fiber. By using the resin composition according to the present embodiment for the secondary resin layer, an optical fiber having excellent lateral pressure characteristics and toughness can be produced.

[0049] <Optical fiber> 1 is a schematic cross-sectional view showing an example of an optical fiber according to the present embodiment. The optical fiber 10 includes a glass fiber 13 including a core 11 and a cladding 12, and a coating resin layer 16 including a primary resin layer 14 and a secondary resin layer 15 provided on the outer periphery of the glass fiber 13.

[0050] The cladding 12 surrounds the core 11. The core 11 and the cladding 12 mainly contain glass such as silica glass, and for example, the core 11 can be made of silica glass doped with germanium or pure silica glass, and the cladding 12 can be made of pure silica glass or silica glass doped with fluorine.

[0051] 1, for example, the outer diameter (D2) of the glass fiber 13 is about 100 μm to 125 μm, and the diameter (D1) of the core 11 constituting the glass fiber 13 is about 7 μm to 15 μm. The thickness of the coating resin layer 16 is usually about 22 μm to 70 μm. The thickness of each of the primary resin layer 14 and the secondary resin layer 15 may be about 5 μm to 50 μm.

[0052] When the outer diameter (D2) of the glass fiber 13 is about 125 μm and the thickness of the coating resin layer 16 is 60 μm to 70 μm, the thickness of each of the primary resin layer 14 and the secondary resin layer 15 may be about 10 μm to 50 μm, for example, the thickness of the primary resin layer 14 may be 35 μm and the thickness of the secondary resin layer 15 may be 25 μm. The outer diameter of the optical fiber 10 may be about 245 μm to 265 μm.

[0053] When the outer diameter (D2) of the glass fiber 13 is about 125 μm and the thickness of the coating resin layer 16 is 27 μm to 48 μm, the thickness of each of the primary resin layer 14 and the secondary resin layer 15 may be about 10 μm to 38 μm, for example, the thickness of the primary resin layer 14 may be 25 μm and the thickness of the secondary resin layer 15 may be 10 μm. The outer diameter of the optical fiber 10 may be about 179 μm to 221 μm.

[0054] When the outer diameter (D2) of the glass fiber 13 is about 100 μm and the thickness of the coating resin layer 16 is 22 μm to 37 μm, the thickness of each of the primary resin layer 14 and the secondary resin layer 15 may be about 5 μm to 32 μm, for example, the thickness of the primary resin layer 14 may be 25 μm and the thickness of the secondary resin layer 15 may be 10 μm. The outer diameter of the optical fiber 10 may be about 144 μm to 174 μm.

[0055] By applying the resin composition according to this embodiment to the secondary resin layer, an optical fiber having a high Young's modulus and excellent lateral pressure characteristics can be produced.

[0056] The manufacturing method of the optical fiber according to this embodiment includes a coating step of coating the above-mentioned resin composition on the outer circumference of a glass fiber composed of a core and a cladding, and a curing step of curing the resin composition by irradiating it with ultraviolet light after the coating step.

[0057] From the viewpoint of improving the lateral pressure characteristics of the optical fiber, the Young's modulus of the secondary resin layer is preferably 1200 MPa or more, more preferably 1400 MPa or more, and even more preferably 1600 MPa or more at 23° C.±2° C. From the viewpoint of imparting appropriate toughness to the secondary resin layer, the Young's modulus of the secondary resin layer is preferably 3500 MPa or less, more preferably 3000 MPa or less, and even more preferably 2500 MPa or less at 23° C.±2° C.

[0058] The primary resin layer 14 can be formed, for example, by curing a resin composition containing a urethane (meth)acrylate, a monomer, a photopolymerization initiator, and a silane coupling agent. The resin composition for the primary coating can be formed using a conventionally known technique. The urethane (meth)acrylate, the monomer, the photopolymerization initiator, and the silane coupling agent may be appropriately selected from the compounds exemplified for the base resin above. However, the resin composition forming the primary resin layer has a different composition from the base resin forming the secondary resin layer.

[0059] In order to prevent the occurrence of voids in the optical fiber, the Young's modulus of the primary resin layer is preferably 0.04 MPa or more and 1.0 MPa or less at 23°C±2°C, more preferably 0.05 MPa or more and 0.9 MPa or less, and even more preferably 0.05 MPa or more and 0.8 MPa or less.

[0060] In some cases, optical fibers are arranged in parallel and integrated with a ribbon resin to form an optical fiber ribbon. The resin composition according to the present disclosure can also be used as a ribbon resin. This can improve the lateral pressure characteristics and toughness of the optical fiber ribbon in the same way as the optical fibers. EXAMPLES

[0061] The present disclosure will be described in more detail below by showing the results of evaluation tests using examples and comparative examples according to the present disclosure. Note that the present disclosure is not limited to these examples.

[0062] (Urethane acrylate) Polypropylene glycol with Mn of 2000, 2,4-tolylene diisocyanate and hydroxyethyl acrylate were reacted to obtain urethane acrylate (UA-1).

[0063] Polypropylene glycol with Mn 4000, isophorone diisocyanate, hydroxyethyl acrylate and methanol were reacted to obtain urethane acrylate (UA-2).

[0064] (Aliphatic epoxy acrylate) As the aliphatic epoxy acrylate, R 1 is a hydrogen atom, and n is 1. 1 is a hydrogen atom, and n is 3. 1 An epoxy acrylate (EA-3) mainly composed of a compound in which R is a hydrogen atom and the average n is about 7, 2 is a hydrogen atom, m is 1, and R in formula (2) is an epoxy acrylate (EA-4) 2 is a hydrogen atom, m is 2, and R in formula (2) is an epoxy acrylate (EA-5) 2 is a hydrogen atom, m is about 4, and R 2 We prepared an epoxy acrylate (EA-7) whose main component is a compound in which is a hydrogen atom and m is approximately 9.

[0065] (Epoxy acrylate having an aromatic ring) As an epoxy acrylate having an aromatic ring, a bisphenol A type epoxy acrylate (EA-8) was prepared.

[0066] (monomer) Tripropylene glycol diacrylate (TPGDA) was prepared as a multifunctional monomer, and 2-phenoxyethyl acrylate (PO-A) was prepared as a monofunctional monomer.

[0067] (Photopolymerization initiator) As photoinitiators, 1-hydroxycyclohexyl phenyl ketone (Omnirad 184) and 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO) were prepared.

[0068] (Inorganic oxide particles) As inorganic oxide particles, a silica sol was prepared in which hydrophobic silica particles having methacryloyl groups and an average primary particle size of 10 to 20 nm were dispersed in MEK.

[0069] [Resin composition for secondary coating] A base resin was prepared by mixing urethane acrylate, epoxy acrylate, monomer, and photopolymerization initiator in the blending amounts (mass%) shown in Table 1 or Table 2. Next, silica sol was mixed with the base resin so as to obtain the silica particle content shown in Table 1 or Table 2, and most of the MEK, which is the dispersion medium, was then removed under reduced pressure to prepare the resin compositions of the examples and comparative examples. The content of MEK remaining in the resin composition was 5 mass% or less.

[0070] In Tables 1 and 2, the numerical values ​​for urethane acrylate, epoxy acrylate, and monomer are the content (mass%) based on the total amount of photopolymerizable compound, and the numerical value for silica particles is the content (mass%) based on the total amount of photopolymerizable compound and silica particles.

[0071] (Young's Modulus) The resin composition obtained in the Examples or Comparative Examples was applied onto a polyethylene terephthalate (PET) film using a spin coater, and then the resin composition was heated to 1000±100 mJ / cm using an electrodeless UV lamp system (Heraeus's "VPS600 (D bulb)"). 2 The resin layer was peeled off from the PET film to obtain a resin film.

[0072] The resin film was punched out into a dumbbell shape conforming to JIS K 7127 Type 5, and pulled at 23±2°C, 50±10% RH, at a pulling speed of 1 mm / min, and with a gauge length of 25 mm, using a tensile tester to obtain a stress-strain curve. Young's modulus was calculated using the 2.5% secant line.

[0073] (Elongation at break) A resin layer with a thickness of 50±5 μm was formed on the PET film by the same operation as in the preparation of the above resin film. The resin layer was peeled off from the PET film to obtain a resin film. The resin film was punched out into a dumbbell shape according to JIS Z 6251 Type 3 and pulled at a tensile speed of 1 mm / min using an INSTRON 5985 material tensile tester under conditions of 23±2°C and 50±10% RH. The breaking elongation was measured using an INSTRON AVE high-precision video extensometer to measure strain.

[0074] [Fabrication of optical fiber] A resin composition for primary coating was obtained by mixing 75 parts by weight of UA-2, 12 parts by weight of nonylphenol EO modified acrylate, 6 parts by weight of N-vinyl caprolactam, 2 parts by weight of 1,6-hexanediol diacrylate, 1 part by weight of Omnirad TPO, and 1 part by weight of 3-mercaptopropyltrimethoxysilane.

[0075] A resin composition for the primary resin layer and a resin composition from an example or comparative example for the secondary resin layer were applied to the outer periphery of a glass fiber having a diameter of 125 μm and composed of a core and cladding, and then the resin compositions were cured by irradiating with ultraviolet light to form a primary resin layer with a thickness of 35 μm and a secondary resin layer with a thickness of 25 μm around its outer periphery, thereby producing an optical fiber.

[0076] (lateral pressure characteristics) The transmission loss of light with a wavelength of 1550 nm was measured using the OTDR (Optical Time Domain Reflectometer) method when optical fiber was wound in a single layer around a 280 mm diameter bobbin covered with sandpaper. The transmission loss of light with a wavelength of 1550 nm was also measured using the OTDR method when optical fiber was wound in a single layer around a 280 mm diameter bobbin without sandpaper. The difference in the measured transmission losses was calculated, and a transmission loss difference of 0.6 dB / km or less was evaluated as "A," and a transmission loss difference of more than 0.6 dB / km was evaluated as "B."

[0077] (Toughness) A 1000m bundle of optical fiber was immersed in mineral oil heated to 85℃ for 30 days, and then the transmission loss of light with a wavelength of 1550nm was measured using the OTDR method. If the difference in transmission loss before and after immersion in mineral oil was 0.04dB / km or less, it was rated as "A", and if it was more than 0.04dB / km, it was rated as "B". If the toughness decreases, the coating is more likely to crack in the mineral oil deterioration test, and the transmission loss increases.

[0078] [Table 1]

[0079] [Table 2] [Explanation of symbols]

[0080] 10 Optical Fiber 11 cores 12 Clad 13 Glass Fiber 14 Primary resin layer 15 Secondary resin layer 16 Coating resin layer

Claims

1. a glass fiber including a core and a cladding; a primary resin layer that is in contact with and covers the glass fiber; A secondary resin layer that covers the primary resin layer, the secondary resin layer includes a cured product of a resin composition including a base resin including a photopolymerizable compound and a photopolymerization initiator, and hydrophobic inorganic oxide particles; The optical fiber, wherein the photopolymerizable compound contains a urethane (meth)acrylate and an aliphatic epoxy (meth)acrylate, and the content of the aliphatic epoxy (meth)acrylate is 1.0 mass% or more and 45 mass% or less based on the total amount of the photopolymerizable compound.

2. The optical fiber of claim 1 , wherein the aliphatic epoxy (meth)acrylate has an ethylene oxide group or a propylene oxide group.

3. 3. The optical fiber according to claim 1, wherein the photopolymerizable compound further comprises an epoxy (meth)acrylate having an aromatic ring.

4. 4. The optical fiber according to claim 1, wherein the inorganic oxide particles are particles containing at least one selected from the group consisting of silicon dioxide, zirconium dioxide, aluminum oxide, magnesium oxide, titanium oxide, tin oxide, and zinc oxide.

5. A coating step of coating a resin composition for a primary resin layer and a resin composition for a secondary resin layer on an outer periphery of a glass fiber composed of a core and a clad; a curing step of curing the resin composition by irradiating it with ultraviolet light after the coating step to form a primary resin layer and a secondary resin layer; Including, the secondary resin layer includes a cured product of a resin composition including a base resin including a photopolymerizable compound and a photopolymerization initiator, and hydrophobic inorganic oxide particles; a method for manufacturing an optical fiber, wherein the photopolymerizable compound contains a urethane (meth)acrylate and an aliphatic epoxy (meth)acrylate, and the content of the aliphatic epoxy (meth)acrylate is 1.0 mass% or more and 45 mass% or less based on the total amount of the photopolymerizable compound.

6. The method for manufacturing an optical fiber described in claim 5, wherein the aliphatic epoxy (meth)acrylate has an ethylene oxide group or a propylene oxide group.

7. A method for manufacturing an optical fiber as described in claim 5 or claim 6, wherein the photopolymerizable compound further contains an epoxy (meth)acrylate having an aromatic ring.

8. A method for manufacturing an optical fiber described in any one of claims 5 to 7, wherein the inorganic oxide particles are particles containing at least one type selected from the group consisting of silicon dioxide, zirconium dioxide, aluminum oxide, magnesium oxide, titanium oxide, tin oxide and zinc oxide.

Citation Information

Patent Citations

  • Ultraviolet-curing resin composition

    JP2000007717A

  • Resin composition for optical fibers coating, and unit using the same

    JP2004045828A

  • Coated optical fiber

    JP2014219550A

  • Liquid curable resin composition for secondary coat layer for optical fiber element wire

    JP2016098127A

  • Optical fiber strand

    WO2017065274A1